New concepts in pathogenesis and management of polycystic ovarian syndrome: Insulin resistance and role of insulin sensitizers - Yadav, Rashmi Prasad (Nepal Journal of Obstetrics and Gynaecology, 2008)
Polycystic ovarian syndrome (PCOS) is classically characterized by the clinical triad of androgen excess, anovulation infertility and obesity. Anovulation occurs due to functional ovarian and/or adrenal hyperandrogenism. The etiology and patho physiology of PCOS is unknown .Proposed theories include excess of gonadotropins; the effect of which is amplified by disturbances in intrinsic regulatory peptides, such as inhibin or extrinsic regulatory peptides, such as insulin or insulin like growth factor ( IGF). For over 25 years insulin resistance has been known to be associated with PCOS. Improvement in insulin resistance with the use of insulin sensitizers, such as metformin and thiazoldinediones (TZDs) have been seen to be associated with better ovulation and reduced testosterone levels in patients with PCOS. Aims: The aim of the present review is to discuss the new concepts in the pathogenesis of PCOS and to know usefulness of insulin sensitizers in such patients. Methods: Over 50 articles extending the span of more than 25 years have been reviewed and an attempt has been made to know the etiopathogenesis of PCOS and also to assess the validity for the uses of insulin sensitizers in patients of PCOS. Results: With the advancement of knowledge regarding etiopathogenesis, the management of PCOS has changed in recent years. In view of positive association between hyperinsulinemia and PCOS, improvement in insulin resistance through weight loss and use of insulin sensitizing drugs has been recommended. Conclusions: Besides symptomatic treatment, recent studies recommend use of insulin sensitizers in management in PCOS for better outcome in them. Key words: Polycystic ovarian syndrome (PCOS), Insulin resistance (IR) Insulin sensitizers (IS). doi:10.3126/njog.v3i1.1431 NJOG 2008 May-June; 3(1): 3 - 9